International Law and Its Impact on the Development of International Organizations - OTHMAN, Adel Hamza (Journal of Advanced Research in Law and Economics; Vol 10 No 8 (2019): JARLE Volume X Issue 8(46) Winter 2019, 2019)
The subject of this paper is the analysis of modern international law, including the elaboration of the main theoretical and practical issues related to its impact on the activities of international organizations as one of the participants in international relations, based on an analysis of regulations, as well as the international law norms and principles of. This paper attempted at carrying out an in-depth analysis of the legal nature of the emergence of international law, describing its qualitative features. In the paper, the author repeatedly emphasizes the extreme importance of international legal issues, which over the past couple of years has gained a special place in the regime of national and international legal systems. Resorting to the analysis of international organizations, periodizations of their occurrence and main priorities of activity, the author touches on foreign policy relations between countries and organizations. The relevance of the subject matter lies in the relativity of the price of international postulates, violation of international law by neglecting the arrangements of legally competent subjects of international law. As a result, the matter of the impact of international law on organizations, which are one of the main sources of its violation, remains understudied. The purpose of this paper is to formulate a systemic concept of interaction and the main forms of influence of international law regarding organizations, member states of organizations, to create proposals for improving the international regulation of organizations and ways of their implementation. The prospects for further study of the subject matter are expressed in an in-depth investigation of the pragmatic angle of the organizations’ activities, compliance with international law while maintaining the full possibility of implementing all the principles of international relations, including the principle of cooperation and the fulfilment in good faith of obligations under international law.